A modified theory of planned behavioral: A case of tourist intention to visit a destination post pandemic Covid-19 in Indonesia. Issue 10 (October 2021) - Pahrudin, Pahrudin; Chen, Chien-Ting; Liu, Li-Wei
Abstract: The Pandemic covid-19 spread globally has been given impact in the tourism industry, especially in the tourism destination. This study investigated to build the concept and theoretical framework that explains the decision of local tourist intention to visit a local destination in Indonesia post-pandemic covid-19. This study was considered the perception of Covid-19, non-pharmaceutical intervention and health consciousness by implying of Theory of Planned Behavior constructs. This study, health consciousness is the moderator variable to predict the decision of tourist to visit a destination. Structural Equation Model-Partial Least Square (SEM-PLS) was used to analyze the construct of study. The model found that the Theory of Planned Behavior was successfully broadened in making the decision of tourist to visit a destination post-covid-19 with considering non-pharmaceutical intervention and health consciousness. The results showed that generally the constructs of Theory Planned Behavior are significantly impacted in intention to visit a local destination in Indonesia, except Hypothesis of subjective norm and intention to visit was rejected. The variable health consciousness through intention to visit also was rejected. The framework also used moderating variable health consciousness between subjective norm and intention to visit was rejected. This study was given insight an issue of covid-19 in the tourism sector, and the implication was providing government, stakeholders, tourism marketers and policy-making with considering non-pharmaceutical and health consciousness during and post-pandemic covid-19. Abstract : Post Covid-19, TPB, Non-Pharmaceutical Intervention, Health Consciousness, Intention to Visit.